Alleviating aluminium toxicity on an acid sulphate soils in Peninsular Malaysia with application of calcium silicate - Azman, Elisa Azura; Ninomiya, Seishi; Jusop, Shamsuddin; Ismail, Roslan (Copernicus Publications, 2015)
In response to human population increase, the utilization of acid sulfate soils for rice cultivation is one option for increasing production. The main problems associated with such soils are their low pH values and their associated high content of exchangeable Al, which could be detrimental to crop growth. The application of soil amendments is one approach for mitigating this problem, and calcium silicate is an alternative soil amendment that could be used. Therefore, the main objective of this study was to ameliorate soil acidity in rice-cropped soil. The secondary objective was to study the effects of calcium silicate amendment on soil acidity, exchangeable Al, exchangeable Ca, and Si content. The soil was treated with 0, 1, 2, and 3 Mg ha−1 of calcium silicate under submerged conditions and the soil treatments were sampled every 30 days throughout an incubation period of 120 days. Application of calcium silicate induced a positive effect on soil pH and exchangeable Al; soil pH increased from 2.9 (initial) to 3.5, while exchangeable Al was reduced from 4.26 (initial) to 0.82 cmolc kg−1. Furthermore, the exchangeable Ca and Si contents increased from 1.68 (initial) to 4.94 cmolc kg−1 and from 21.21 (initial) to 81.71 mg kg−1, respectively. Therefore, it was noted that calcium silicate was effective at alleviating Al toxicity in acid sulfate, rice-cropped soil, yielding values below the critical level of 2 cmolc kg−1. In addition, application of calcium silicate showed an ameliorative effect as it increased soil pH and supplied substantial amounts of Ca and Si.